43. Open Source Software: Fully featured vs. “the devil you know” - Hotrum, Michael; Ludwig, Brian; Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2005)
The ILIAS learning management system (LMS) was evaluated, following its favourable rating in an independent evaluation study of open source software (OSS) products. The current review found ILIAS to have numerous features of value to distance education (DE) students and teachers, as well as problems for consideration in the system’s ongoing development. The current findings were compared with DE students’ reactions to a similar LMS product, ATutor, also rated highly in the independent OSS evaluation. In comparing an ATutor course website with a simple HTML-based version of the same site, the ten students voted unanimously to retain the simpler site. This result is consistent with previous evaluation findings in the current series of reports, and indicates that increasing integration of product features does not necessarily improve a product’s ease of use or educational effectiveness.